Efficacy and safety of radiotherapy/chemoradiotherapy combined with immune checkpoint inhibitors for locally advanced stages of esophageal cancer: A systematic review and meta-analysis - Wu, Jing; Deng, Rong; Ni, Tingting; Zhong, Qin; Tang, Fei; Li, Yan; Zhang, Yu (Frontiers in Oncology, 2022)
Background: Radiotherapy (RT)/Chemoradiotherapy (CRT) are an important treatment for all stages of esophageal cancer (EC). The combination of immune checkpoint inhibitors (ICIs) to RT/CRT seems to be promising avenue for the treatment of EC. Therefore, a systematic review and meta-analysis was performed in order to assess the safety and efficacy of RT/CRT and ICI combination therapy for EC patients. Methods: PubMed and several other databases were searched (according to specific criteria) to find relevant studies published prior to the 31st of December 2021. Results: 1962 articles were identified for screening and six trials containing 668 patients were identified and pooled to determine the one- and two-year overall survival (OS), which were 84.5% (95% confidence interval (CI): 69.9%-100%) and 68.3% (95% CI: 49.0%-95.1%), respectively. Additionally, the rate of pooled grade 3-5 adverse reaction was 41.0% (95% CI: 31.2%-51.2%). The rate of specific grade 3-5 adverse reactions are as follows: lymphopenia (36.8%-60%), esophagitis (20%), anastomotic leakage (18%), esophageal fistula (10%), pain (10%), leukopenia (5.3%-10%), esophageal hemorrhage (2.5%-5%), chyle leakage (3%), fatigue (5%), cough (2.7%-5%), diarrhea (2.7%), pulmonary embolism (2.5%) and allergic reaction (2.5%). The pooled rate of pneumonitis of grade 3-5 and grade 1-5 was 0.8% (95% CI: 0.1%-0.16%, I2: 0%) and 5.4% (95% CI: 2.0%-14.2%, I2: 82%). For thoracic complication, esophagitis was 63.6% (95% CI: 42.4%-80.6%), which appeared to be more frequent with the combination of ICIs to RT/CRT (12%-37.7%). Other thoracic complications include esophageal hemorrhage (2.5%-10%), esophageal fistula (6%-10%) and anastomotic leakage (6%-21%). Additionally, some of the trials did not report cardiac related adverse reactions. The subgroup analyses also revealed that the pooled rate patients with grade 3-5 pneumonitis was higher for CRT/RT with concurrent and sequential ICI treatment (1.9%) than other groups (0.8%). Conclusion: This study suggests that the addition of ICIs to RT/CRT for EC patients may be both safe and feasible. However, larger randomized studies are needed to confirm these results.